Unveiling sialoglycans’ immune mastery in pregnancy and their intersection with tumor biology - Jianmei Huang; Lu Feng; Jianming Huang; Guonan Zhang; Shixiu Liao (Frontiers in Immunology)
Sialylation is a typical final step of glycosylation, which is a prevalent post-translational modification of proteins. Sialoglycans, the products of sialylation, are located on the outmost of cells and participate in pivotal biological processes. They have been identified as glyco-immune checkpoints and are currently under rigorous investigation in the field of tumor research. It is noteworthy that the exploration of sialoglycans in tumor and pregnancy contexts was both initiated in the 1960s. Mechanisms in these two conditions exhibit similarities. Trophoblast infiltration during pregnancy gets controlled, while tumor invasion is uncontrolled. The maternal-fetal immunotolerance balances acceptance of the semiallogeneic fetus and resistance against “non-self” antigen attack simultaneously. Tumors mask themselves with sialoglycans as “don’t eat me” signals to escape immune surveillance. The trophoblastic epithelium is covered with sialoglycans, which have been demonstrated to play an immune regulatory role throughout the entire pregnancy. Immune abnormalities are commonly recognized as an important reason for miscarriages. Therapeutic strategies that desialylation and targeting receptors of sialoglycans have been studied in tumors, while agents that target glyco-immune checkpoints have not been studied in pregnancy. Thus, investigating the roles of sialoglycans in pregnancy and their intersection with tumors may facilitate the development of novel therapies targeting glyco-immune checkpoints for the treatment of pregnancy-related diseases, such as miscarriage and preeclampsia.